The impact of electronic planning management in improving the quality of nursing care in Baghdad hospitals - jasim, basima; ali, najem (Iraqi National Journal of Nursing Specialties, 2012)
Management is considered as most important resource of the society ones in modern era and an exchange point in societies’ lives in order to achieve its goals and wishes. So far, management behinds the new electronic society has become different in shape and nature due to the force of the nature of information technology that shapes the relationships between the world’s individuals at the national level but it goes beyond the international ones. The study aims at identifying the impact of the electronic management’s components upon the improvement of the quality of nursing care in Baghdad’s hospitals. The descriptive design, with a sample-survey approach, is used as appropriate ones for the field study of social phenomena. So, it presents data about these phenomena and the relations between their reasons, results and analysis to depict the effective factors in them. The study uses a questionnaire for data collection from the respondents. It is comprised of (31) items which are distributed on two parts; first, demographic characteristics (8) items and second, electronic management’s components with a five levels Likert Scale of strongly disagree, disagree, uncertain, agree, and strongly agree with a rating scale of 1 for strongly disagree, 2 for disagree, 3 for uncertain, 4 for agree, and 5 for strongly agree, respectively. Validity of the questionnaire is determined through its administration to panel of (10) experts who are specialists to present their judgments about its content validity. Reliability of the questionnaire is determined through the use reliability coefficients to achieve its internal consistency. Data are collected through field visits to the hospitals and interviews with subjects. The setting of the study includes all hospitals in Baghdad City which are (43) hospitals. These hospitals are distributed on three health directorates as; (8) for Medical City Directorate, (13) for Al-Karkh Health Directorate, and (22) for Al-Rusafa Health Directorate. The sample is consisted of (43) nurse manager and (101) head nurse. It is purposive “non-probability” ones and it is selected with respect to the selection criteria of number of years in nursing and number of years in nursing management for no less than one year. Data of the study are analyzed through descriptive data analysis approach, cluster analysis and factor analysis. The study reveals that variables that include age, gender, level of education, place of work, number of years in nursing, number of years in nursing management, years of experience in electronic management and the duration of each training session in nursing management have an impact in improving the quality of nursing management. The findings indicate that electronic planning management plays more effective role in the future of the electronic management and the quality of operating nursing care. So far, we provide sufficient answers to all questions and hypotheses that the present study has presented. The study recommends that there is necessity to prepare and implement specialized programs which are concerned in electronic management for the preparation of managerial leaders in this field. Being relied on electronic learning curriculum in general and specifically electronic management in nursing courses with respect to what have been accomplished in developed nations’ universities. Nursing staff have to be encouraged for enrollment in educational and training sessions as being relative to electronic management. Reporting, monitoring, evaluation and promotion for participants system can be initiated. National comprehensive studies that depend on comparison and targeted large number of health organizations in public and private sectors, and nursing staff for identification of barriers for the implementation and presentation of the recommendations, solutions, and the appropriate approaches that develop technical, managerial and leadership aspects. Concern can be presented with regard to training sessions in the field of electronic management, especially that of electronic planning management.